Organic / inorganic hybrid nano-material, fireproof pre-reaction liquid, and preparation method and application of fireproof pre-reaction liquid
By using polyacrylamide group with multi -layer nuclear shell structure and multiple cross -linking characteristics, organic/inorganic hybrid nanomaterials solves the problem of UV -resistant and weather resistance of existing flame retardant fireproof transparent coating. Realize high -performance fireproof coating.
Patent Information
- Application Number
- CN202411499258.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-25
AI Technical Summary
The existing flame-retardant fire-resistant transparent coating prereaction has poor UV radiation resistance, which leads to cracking and falling off under long-term outdoor radiation, and has poor solvent resistance, hardness, low temperature resistance and impact resistance. Impacts actual fire protection effect and service life.
Adopt a polyacrylamide group that has a "spiny pear" multi -layer nuclear shell structure and a multi -cross -cross -cross -cross -linked co -organic/inorganic hybrid nanoma material. By introducing double bonds and aminels on the surface of hydrophilic silicon dioxide to achieve linear polymer Branching forms multiple cross -linking network structures to improve the weather resistance and fire resistance of coating.
It significantly improves the resistance of UV-resistant, impact resistance, hardness and water resistance of the fire layer, extend the service life, and meet the flame retardant standards of DIN4102 B1 and UL94-V0.
Smart Images

Figure CN119371690A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of glass safety, and in particular to an organic / inorganic hybrid nano material, a fireproof pre-reaction liquid, and a preparation method and application thereof. Background Art
[0002] As urbanization progresses at an increasingly rapid pace, the building windows of houses are becoming larger and larger. Elegant, beautiful, and functional glass components are gradually gaining favor among designers at home and abroad, which directly leads to the rapid development of various types of safety glass and special glass in the architectural glass industry. Architectural glass has gradually developed from being a simple lighting and decorative material to having multiple functions such as light control, room temperature regulation, noise reduction, and improvement of living environment. Special coatings have gradually developed from being a simple anti-corrosion and decorative material to having multiple functions such as flame retardancy, heat insulation, wear resistance, damping, and noise reduction.
[0003] As a safe coating, flame retardant fireproof transparent coating pre-reaction liquid not only has some properties of ordinary coatings, but also has the properties of controlling the spread of fire and heat insulation, which provides valuable rescue time for effective rescue in the event of a fire, minimizes the loss of personnel, property and vehicles, and reduces the destructive power of the fire to a minimum. Fireproof glass can be formed by coating on the surface of glass. In addition to some properties of ordinary glass, coated fireproof glass can also protect escape and rescue personnel from heat radiation damage. Due to the recent frequent fires in some well-known large buildings at home and abroad, people have gradually begun to pay attention to the research and development, production and use effects of new flame retardant coatings. Poor ultraviolet radiation resistance is one of the main factors restricting the application of flame retardant coatings. Therefore, it is an important direction for the industrialization development of special coatings to develop high-performance flame retardant fireproof transparent coating pre-reaction liquid with excellent ultraviolet radiation resistance to achieve a qualitative leap in product performance and expand the application area of the product.
[0004] At present, the work done in China on flame-retardant fireproof transparent coating pre-reaction liquid for glass is at the basic research stage. The existing flame-retardant fireproof transparent coating pre-reaction liquid has poor ultraviolet radiation resistance and needs to be applied frequently and regularly, with a large amount of fireproof coating. At the same time, most products will crack and fall off from the glass surface under long-term outdoor ultraviolet radiation, and cannot meet the requirements for long-term outdoor use in the rainy southern regions; the existing flame-retardant coating also has poor solvent resistance, hardness, low temperature resistance, and impact resistance, which reduces the actual fireproof effect of the fireproof layer and seriously affects the use effect and service life of the flame-retardant fireproof transparent coating pre-reaction liquid. Summary of the invention
[0005] The main purpose of the present invention is to provide a polyacrylamide-based organic / inorganic hybrid nanomaterial with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking, a fire-proof pre-reaction liquid and a preparation method and application thereof, which overcomes the disadvantages of the fire-proof layer material in the prior art that cannot meet the ultraviolet test, and avoids the shortcomings of cracking of the fire-proof layer, mismatch between impact resistance and hardness, and poor water resistance.
[0006] The purpose of the present invention and the solution to the technical problem are achieved by adopting the following technical solutions.
[0007] The organic / inorganic hybrid nanomaterial comprises a first polyacrylamide-based organic / inorganic hybrid nanoparticle and a second polyacrylamide-based organic / inorganic hybrid nanoparticle, wherein the first polyacrylamide-based organic / inorganic hybrid nanoparticle and the second polyacrylamide-based organic / inorganic hybrid nanoparticle both comprise a flexible core layer, a shell layer and a reinforcing transition layer, wherein the reinforcing transition layer is arranged between the flexible core layer and the shell layer; wherein the shell layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle is a polymer layer containing a phosphorus polymer, and the surface of the shell layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle is grafted with linear ammonium polyphosphate, and the shell layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticle is a polymer layer containing an epoxy polymer, and the surface of the shell layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticle is grafted with linear polymethyl methacrylate. The invention relates to polyacrylamide based organic / inorganic hybrid nanoparticles, wherein the flexible core layer of the first polyacrylamide based organic / inorganic hybrid nanoparticles and the flexible core layer of the second polyacrylamide based organic / inorganic hybrid nanoparticles are both polyacrylamide latex particles, the reinforcing transition layer of the first polyacrylamide based organic / inorganic hybrid nanoparticles and the reinforcing transition layer of the second polyacrylamide based organic / inorganic hybrid nanoparticles are both polymer layers containing melamine formaldehyde material with a cross-linked network structure; the polymer in the shell layer of the first polyacrylamide based organic / inorganic hybrid nanoparticles and the polymer in the shell layer of the second polyacrylamide based organic / inorganic hybrid nanoparticles both contain at least one polymer that can form an interpenetrating network structure with cellulose, and in the present invention, both linear polymethacrylate glycidyl ester and linear ammonium polyphosphate can form an interpenetrating network structure with cellulose;
[0008] The material composed of the first polyacrylamide-based organic / inorganic hybrid nanoparticles is made of the following components: 7 to 26 parts by weight of a third mixed solution and 51 to 327 parts by weight of a second polymer template emulsion; the third mixed solution is made by mixing 5 to 15 parts by weight of ammonium polyphosphate, 0.1 to 1 parts by weight of ethanol and 2 to 10 parts by weight of deionized water; the second polymer template emulsion is made by mixing 0.1 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silicon dioxide dispersion with amino groups on the surface, 0.003 to 0.03 parts by weight of an initiator and 26 to 243 parts by weight of the first polymer template emulsion; the second mixed solution is made by mixing 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid and 0.01 to 0.02 parts by weight of a reactive emulsifier; the first polymer template emulsion is made by mixing 0.5 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water, 10 to 26 parts by weight of a silicon dioxide dispersion with amino groups on the surface, 0.003 to 0.03 parts by weight of an initiator and 26 to 243 parts by weight of a first polymer template emulsion. The first mixed solution is prepared by mixing 0.1-20 parts by weight of butyl acrylate, 0.1-20 parts by weight of melamine, 0.1-20 parts by weight of styrene, 0.01-0.03 parts by weight of divinyl sulfone, 0.05-0.2 parts by weight of 20wt% ammonia water, 0.1-20 parts by weight of tantalum, and 0.1-20 parts by weight of tantalum. 1. The silica seed solution is prepared by mixing 10-25 parts by weight of silica seed solution, 0.1-1 parts by weight of amino silane coupling agent and 0.001-0.02 parts by weight of ethanol; and 2-3 parts by weight of tetraethyl orthosilicate, 0.02-0.04 parts by weight of concentrated ammonia water with a concentration of 25wt% and 8-22 parts by weight of deionized water.
[0009] The material composed of the second polyacrylamide-based organic / inorganic hybrid nanoparticles is made of the following components: 10 to 25 parts by weight of the fourth mixed solution and 51 to 327 parts by weight of the fourth polymer template emulsion; the fourth mixed solution is mixed with 5 to 15 parts by weight of glycidyl methacrylate, 0.01 to 0.2 parts by weight of initiator and 5 to 10 parts by weight of deionized water; the fourth polymer template emulsion is made of 0.1 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of silica dispersion with double bonds on the surface, 0.003 to 0.03 parts by weight of initiator and 26 to 243 parts by weight of the first polymer template emulsion; the second mixed solution is mixed with 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid and 0.01 to 0.02 parts by weight of reactive emulsifier; the first polymer template emulsion is mixed with 0.1 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water, 10 to 26 parts by weight of silica dispersion with double bonds on the surface, 0.003 to 0.03 parts by weight of initiator and 26 to 243 parts by weight of the first polymer template emulsion. The first mixed solution is prepared by mixing 0.1-20 parts by weight of butyl acrylate, 0.1-20 parts by weight of melamine, 0.1-20 parts by weight of styrene, 0.01-0.03 parts by weight of divinyl sulfone, 0.05-0.2 parts by weight of 20wt% ammonia water, 0.1-2 The invention discloses a method for preparing a hydrophilic silica dispersion liquid comprising: a silica seed solution and a silica slurry; a silica seed solution and a silica slurry comprising: a silica slurry comprising: 10 to 25 parts by weight of a silica seed solution, 0.1 to 1 parts by weight of an aminosilane coupling agent, and 0.001 to 0.02 parts by weight of ethanol; and a silica seed solution and a silica slurry comprising: 2 to 3 parts by weight of ethyl orthosilicate, 0.02 to 0.04 parts by weight of concentrated ammonia water with a concentration of 25 wt %, and 8 to 22 parts of deionized water.
[0010] The above-mentioned organic / inorganic hybrid nanomaterial is characterized in that the degree of polymerization of the polyacrylamide particles in the polyacrylamide emulsion is 10,000 to 100,000, the particle size is 40 nm to 200 nm, and the particle size distribution is a single-peak narrow distribution.
[0011] In the above organic / inorganic hybrid nanomaterial, the alkenyl silane coupling agent is one or more of vinyl tert-butyl triperoxide silane, vinyl triethoxy silane, butadienyl triethoxy silane, vinyl trimethoxy silane, isobutylenyl triethoxy silane and vinyl tri(β-methoxyethoxy) silane.
[0012] In the above organic / inorganic hybrid nanomaterial, the aminosilane coupling agent is one or more of the silanes selected from the group consisting of phenylaminomethyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β (aminoethyl)-γ-aminopropyltriethoxysilane and 3-aminopropyltriethoxysilane.
[0013] The initiator of the organic / inorganic hybrid nanomaterial is one or both of a thermal initiator and a redox initiator.
[0014] The method for preparing the above organic / inorganic hybrid nanomaterial comprises the following steps:
[0015] S11) preparing a silicon dioxide seed solution: mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm;
[0016] S12-1) preparing a silica dispersion with amine groups on the surface: placing a silica seed solution, an amino-silane coupling agent and ethanol in a weight ratio of 10 to 25: 0.1 to 1: 0.001 to 0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes to obtain a first primary dispersion, placing the first primary dispersion in a three-necked flask, and then placing the three-necked flask in a water bath at 70°C to 90°C, stirring and dispersing at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooling to 20°C to obtain a silica dispersion with amine groups on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11);
[0017] S12-2) preparing a silica dispersion with double bonds on the surface: placing a silica seed solution, an alkenyl silane coupling agent and ethanol in a weight ratio of 10 to 25: 0.1 to 1: 0.001 to 0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes to obtain a second primary dispersion, placing the second primary dispersion in a three-necked flask, and then placing the three-necked flask in a water bath at 70°C to 90°C, stirring and dispersing at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooling to 20°C to obtain a silica dispersion with double bonds on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11);
[0018] S13) preparing a first polymer template emulsion, the specific steps are as follows:
[0019] S13-1) mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt % ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and a reactive emulsifier in a weight ratio of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution;
[0020] S13-2) By means of starvation polymerization, 0.5 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water and 0.005 to 1 part by weight of an initiator are added dropwise to 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure;
[0021] S14) preparing an emulsion containing first polyacrylamide-based organic / inorganic hybrid nanoparticles, the specific steps are as follows:
[0022] S14-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.01-0.02 parts to prepare a second mixed solution;
[0023] S14-2) preparing a second polymer template emulsion: by means of starvation polymerization, at a temperature of 60 to 65° C., 0.1 to 18 parts by weight of a second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having amino groups on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 243 parts by weight of a first polymer template emulsion at a constant speed. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silica particles having an amino group and a particle size of 20 nm to 30 nm is coated on the surface of the polyacrylamide latex particles, thereby obtaining a second polymer template emulsion having a bayberry-like multilayer core-shell structure;
[0024] S14-3) preparing a third mixed solution: mixing ammonium polyphosphate, ethanol and deionized water in a weight ratio of 5-15:0.5-1:2-10 to prepare a third mixed solution;
[0025] S14-4) preparing an emulsion containing first polyacrylamide-based organic / inorganic hybrid nanoparticles: by means of an ion exchange reaction, 7 to 26 parts by weight of the third mixed solution are added dropwise to 51 to 327 parts by weight of the second polymer template emulsion at a constant speed at a temperature of 30 to 40° C., stirred at a stirring speed of less than 80 r / min, and refluxed under this temperature for 4 hours to form a polymer with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles, thereby obtaining an emulsion containing first polyacrylamide-based organic / inorganic hybrid nanoparticles;
[0026] S15) preparing an emulsion containing a second polyacrylamide-based organic / inorganic hybrid nanoparticle, the specific steps are as follows:
[0027] S15-1) preparing a third polymer template emulsion: by means of starvation polymerization, at a temperature of 60 to 65° C., 0.1 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having double bonds on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 242 parts by weight of the first polymer template emulsion at a constant speed. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material embedded with silica particles having a particle size of 20 nm to 30 nm and having double bonds is coated on the surface of the polyacrylamide latex particles, thereby obtaining a third polymer template emulsion having a multilayer core-shell structure;
[0028] S15-2) preparing a fourth mixed solution: preparing a fourth mixed solution by mixing glycidyl methacrylate, an initiator and deionized water in a weight ratio of 5-15:0.01-0.2:5-10;
[0029] S15-3) preparing an emulsion containing second polyacrylamide-based organic / inorganic hybrid nanoparticles: adding 10 to 25 parts by weight of the fourth mixed solution to 51 to 327 parts by weight of the third polymer template emulsion at a constant speed at a temperature of 60 to 65° C., stirring at a stirring speed of less than 80 r / min, and reflux condensing for 3 hours at this temperature to form a second polymer with linear polymethacrylate glycidyl ester as a branch on the surface of the latex particles, thereby obtaining an emulsion containing second polyacrylamide-based organic / inorganic hybrid nanoparticles;
[0030] S16) Compounding the emulsion containing the first polyacrylamide-based organic / inorganic hybrid nanoparticles and the emulsion containing the second polyacrylamide-based organic / inorganic hybrid nanoparticles to obtain an organic / inorganic hybrid nanomaterial.
[0031] The fire-proof pre-reaction liquid comprises at least the following components: 58 to 353 parts by weight of a first polyacrylamide-based organic / inorganic hybrid nanoparticles, 61 to 352 parts by weight of a second polyacrylamide-based organic / inorganic hybrid nanoparticles, 0.5 to 4 parts by weight of a cellulose solvent, 0.5 to 2.5 parts by weight of a catalyst, and 10 to 30 parts by weight of deionized water; the first polyacrylamide-based organic / inorganic hybrid nanoparticles are the first polyacrylamide-based organic / inorganic hybrid nanoparticles described in claim 1, and the second polyacrylamide-based organic / inorganic hybrid nanoparticles are the second polyacrylamide-based organic / inorganic hybrid nanoparticles described in claim 1.
[0032] The above-mentioned fire-proof pre-reaction liquid also includes: 1 to 5 parts by weight of a carbonizing agent, 0.001 to 0.05 parts by weight of a defoaming agent and 0.1 to 1 parts by weight of a rheological additive; the carbonizing agent is compounded by pentaerythritol and one or more of sucrose, fructose, glucose and maltose; the rheological additive is one or more of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the antifreeze plasticizer is one or more of ethylene glycol, glycerol and 1,4-butanediol; the cellulose solvent is one or both of dipropylene glycol methyl ether and N-methylmorpholine oxide; the catalyst is compounded by a dilute hydrochloric acid solution with a mass concentration less than or equal to 20wt% and one or both of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite; the defoaming agent is one or both of a polysiloxane defoaming agent and a polyether defoaming agent.
[0033] The method for preparing the fire-proof pre-reaction liquid comprises the following steps:
[0034] Step S21), a carbonizing agent, a rheological additive, and deionized water are mixed in a weight ratio of 1-5:0.1-1:10-25, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and allowed to stand for 12 hours to obtain a transparent and dynamically reversible gel material;
[0035] Step S22) The first polyacrylamide-based organic / inorganic hybrid nanoparticles, the second polyacrylamide-based organic / inorganic hybrid nanoparticles, the cellulose solvent, the catalyst and the deionized water are mixed in a weight ratio of 58-353:61-352:0.5-4:0.5-2.5:10-30 to obtain a first fireproof mixed solution,
[0036] Stir at room temperature at a stirring speed of less than 80r / min for 40 minutes to form a uniform suspension; then add 11 to 30 parts by weight of gelling material to the first fire-proof mixed liquid, and stir at room temperature at a stirring speed of less than 80r / min for 80 minutes to obtain a clear or slightly turbid second fire-proof mixed liquid; then add 0.5 to 2.5 parts by weight of catalyst and 0.001 to 0.05 parts by weight of defoaming agent to the second fire-proof mixed liquid in sequence, and stir at room temperature at a stirring speed of less than 80r / min for 40 minutes to obtain a fire-proof pre-reaction liquid, and let it stand for use.
[0037] The above-mentioned fire-retardant pre-reaction liquid is used for flame retardant treatment of transparent cellulose modified soda-lime glass products and forming a fire-retardant layer with a thickness of 0.02 to 0.3 mm on the surface of the glass products. The specific operation is: spray the fire-retardant pre-reaction liquid onto the surface of the transparent cellulose modified soda-lime glass product, let it stand for 50 minutes, and after the surface of the glass product is dry, put it into a 50°C oven for baking for 4 hours, and then heat it to 80°C and bake for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure.
[0038] The technical solution of the present invention achieves the following beneficial technical effects:
[0039] 1. By introducing double bonds (alkenyl silane coupling agent) and amine groups (amino silane coupling agent) on the hydrophilic silica surface, reaction sites are provided for grafting the two outermost linear polymers (ammonium polyphosphate and poly(glycidyl methacrylate)) onto the core-shell polymer surface: the amine groups in the functional shell polymer can graft ammonium polyphosphate onto the functional shell surface through an ion exchange reaction in an ethanol solution to obtain linear grafted ammonium polyphosphate; at the same time, the alkenyl groups in the functional shell can undergo polymerization reaction with glycidyl methacrylate to form a linear poly(glycidyl methacrylate) polymer, which provides a precursor for the subsequent ring-opening and curing of epoxy groups with ionic reaction activity, thereby forming a material with a multiple network structure; the use of cellulose-based substances as rheological additives in the fire-retardant pre-reaction liquid can improve the leveling of the system during brushing, and can also penetrate into multiple cross-linked networks to form physical cross-links, thereby further entangled with the cellulose on the surface of transparent cellulose-modified soda-lime glass for construction, thereby improving the cross-linking degree of the coating.
[0040] 2. The introduction of polyacrylamide in the flexible core layer, silica particles in the functional shell layer, and cross-linking agent divinyl sulfone ensures the toughness, impact strength, hardness and environmental adaptability of the coating: Since glass windows are subject to wiping, wind deformation and weather resistance during use, the silica particles in the polymer functional shell layer further improve the toughness and impact strength of the system on the basis of the original multiple cross-linking. At the same time, the introduction of the multiple cross-linking system also provides conditions for improving the weather resistance of organic coatings for glass windows.
[0041] 3. By using soap-free emulsification technology to gradually polymerize, the amount of emulsifier is further optimized by introducing reactive emulsifiers; at the same time, compared with the blended fire-retardant pre-reaction liquid, the hydrophilic groups in the monomer are effectively distributed in each layer of the latex particles by using the particle design principle, which reduces the number of hydrophilic groups concentrated and distributed in the outermost layer, thereby reducing the viscosity of the solution, making it easier to penetrate the inside of the transparent lignin layer on the glass surface, and improving the flame retardancy of the product; by using ion exchange method and low-temperature polycondensation method, ammonium polyphosphate and melamine formaldehyde are grafted to the surface and surface of latex particles respectively at a temperature below 50°C. In the reinforcing transition layer, the cross-linked network structure is avoided from being formed in the pre-reaction liquid in advance. At the same time, after being coated on the glass surface in the later stage, the gradient heating method is used to produce a synergistic effect between the components in the fire-retardant pre-reaction liquid, thereby ensuring the realization of the functions of the multiple cross-linking system. A high-performance flame-retardant fire-resistant glass material is prepared, which can be used in a low-temperature environment of -25°C±1°C, has a coating that is resistant to ultraviolet radiation for more than 2000 hours, and a flame retardant grade that meets the B1 low flammability material standard specified in DIN4102 (German standard) and the UL94-V0 high flame retardant material standard (American Insurance Association standard).
[0042] 4. The fireproof layer formed after the fireproof pre-reaction liquid of the present invention is cured has the characteristics of resistance to low temperature, resistance to ultraviolet radiation, resistance to impact, high hardness and resistance to water washing. The reason is that the specially designed multi-layer core-shell structure and preparation process optimize the effective cross-linking of the particles themselves and between particles, reduce the swelling degree of the multi-layer core-shell latex particles and the film layer, such as the solvent in the system and the moisture in the use environment, further improve the density of the particles in the film forming process, and reduce the moisture content in the film layer on the basis of improving the strength of the film polymer. Correspondingly, the destruction of the internal structure of the film layer by ice crystals at low temperatures is avoided; the multiple cross-linking system also increases the ultraviolet radiation resistance of the film layer; at the same time, silica particles with double bonds and amine groups are polymerized in the functional shell layer, which is effective. The "sea buckthorn"-shaped linear ammonium polyphosphate and poly(glycidyl methacrylate) molecular chains are evenly distributed on the outer surface of the latex particles. At the same time, with the help of the high hardness of the silica inorganic particles, the advantage of the "soft core and hard shell" of the latex particles is achieved. The soft core can ensure that the coating has excellent impact resistance, and the organic\inorganic composite hard shell with a cross-linked structure gives the coating scratch resistance and can also improve the coating's resistance to ultraviolet radiation; the "sea buckthorn"-shaped structure increases the entanglement between the film layer and the transparent cellulose on the glass surface, and the multiple network cross-linked structures firmly fix these entanglements together, thereby improving the adhesion of the coating. At the same time, this "sea buckthorn"-shaped structure can give the coating a "lotus effect", further improving the coating's resistance to water washing.
[0043] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Schematic diagram of the structure of the first polyacrylamide-based organic / inorganic hybrid nanoparticles.
[0045] Figure 2 Schematic diagram of the structure of the second polyacrylamide-based organic / inorganic hybrid nanoparticles.
[0046] 1-flexible core layer; 2-reinforced transition layer; 3-shell layer; 4-silicon dioxide particles; 5-linear ammonium polyphosphate polymer; 6-linear glycidyl methacrylate polymer. DETAILED DESCRIPTION
[0047] The organic / inorganic hybrid nanomaterial of the present invention is composed of two polyacrylamide-based organic / inorganic hybrid nanoparticles. Figure 1 and Figure 2As shown, in the multi-layer core-shell structure of each polyacrylamide-based organic / inorganic hybrid nanoparticle, a reinforcing transition layer is provided between the flexible core layer and the outermost shell layer, the reinforcing transition layer is a polymer layer containing melamine formaldehyde material with a cross-linked network structure, and in the two polyacrylamide-based organic / inorganic hybrid nanoparticles, the outermost layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle is a graft formed by a phosphorus-containing polymer, and the outermost layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticle is a graft formed by an epoxy-containing polymer, wherein the graft of the outermost layer of the polyacrylamide-based organic / inorganic hybrid nanoparticle is similar to the thorns on the surface of the sea buckthorn; at least one polymer in the two polyacrylamide-based organic / inorganic hybrid nanoparticles can form a fireproof layer of an interpenetrating network structure with cellulose. Among them, the polyacrylamide-based organic / inorganic hybrid nanoparticles with a multilayer core-shell structure are narrowly distributed particles prepared by a soap-free emulsion polymerization method and with the help of particle design principles. For the first polyacrylamide-based organic / inorganic hybrid nanoparticles, the flexible core layer material is polyacrylamide particles and their aggregates, and the materials wrapped on the polyacrylamide particles are respectively a reinforcing transition layer of a cross-linked poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer, a poly(butyl acrylate-methyl methacrylate-methacrylic acid) inlaid with silica particles with a particle size of 20nm to 30nm and amino groups, and a reinforcing transition layer of a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm and amino groups. The invention relates to a shell layer of a copolymer and a shell surface graft composed of linear ammonium polyphosphate; for the second polyacrylamide-based organic / inorganic hybrid nanoparticles, the flexible core layer material is polyacrylamide particles and their aggregates, and the materials wrapped on the polyacrylamide particles are respectively a reinforcing transition layer of a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer with a cross-linked structure, a shell layer of a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm and double bonds, and a shell graft composed of a linear poly(glycidyl methacrylate) copolymer.The fireproof pre-reaction liquid containing the organic / inorganic hybrid nanomaterial is composed of the following substances in parts by weight: 4-6 parts of tetraethyl orthosilicate, 0.04-0.08 parts of concentrated ammonia water with a concentration of 25wt%, 55-138 parts of deionized water, 0.1-1 parts of alkenyl silane coupling agent, 0.1-1 parts of amino silane coupling agent, 0.502-1.04 parts of ethanol, 40-300 parts of polyacrylamide solution, 0.4-52 parts of butyl acrylate, 1.2-14 parts of methyl methacrylate, 0.2-40 parts of melamine, 0.2-4 0 parts, divinyl sulfone 0.02-0.06 parts, 20wt% ammonia water 0.1-0.4 parts, 2,4-methyl-3-cyclohexene carboxaldehyde 0.2-40 parts, methacrylic acid 0.2-12 parts, ammonium polyphosphate 5-15 parts, glycidyl methacrylate 5-15 parts, emulsifier 0.024-0.2 parts, initiator 0.026-2.26 parts, carbonizing agent 1-5 parts, rheological additive 0.1-1 parts, cellulose solvent 0.5-4, catalyst 0.5-2.5 parts, defoaming agent 0.001-0.05 parts. The polyacrylamide-based organic / inorganic hybrid nanoparticles are single-peak, narrowly distributed particles; the polyacrylamide-based organic / inorganic hybrid nanoparticles with a nano core-shell structure are narrowly distributed particles prepared by a soap-free emulsion polymerization method and a particle design principle. For the first polyacrylamide-based organic / inorganic hybrid nanoparticles, the flexible core layer material is polyacrylamide particles and aggregates thereof, the reinforcing transition layer material is a cross-linked poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer, and the shell layer material is a poly(butyl acrylate-methyl methacrylate- The shell layer is a kind of organic / inorganic hybrid nanoparticles, wherein the material of the flexible core layer is polyacrylamide particles and aggregates thereof, the material of the reinforcing transition layer is a cross-linked poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer, the shell layer material is a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm and double bonds, and the shell layer surface graft is a linear poly(glycidyl methacrylate) copolymer; the pH value of the pre-reaction liquid of the fireproof material is between 5.5 and 8.5.
[0048] like Figure 1 and Figure 2As shown, the shell layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticles and the shell layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticles in the present invention both contain silicon dioxide particles. Since the hardness of silicon dioxide particles is relatively large compared to the hardness of organic matter, the silicon dioxide in the shell layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticles and the shell layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticles can further improve the strength of the shell layer, and while the inner layer structure provides toughness, it can ensure that the material has beneficial impact resistance and can also ensure the strength of the material.
[0049] As a preferred embodiment, the fire-proof pre-reaction liquid is composed of the following raw materials, in parts by weight: 4.5-5.5 parts of tetraethyl orthosilicate, 0.05-0.07 parts of concentrated ammonia water with a concentration of 25wt%, 60-120 parts of deionized water, 0.2-0.8 parts of alkenyl silane coupling agent, 0.2-0.8 parts of amino silane coupling agent, 0.6-0.9 parts of ethanol, 30-120 parts of polyacrylamide solution, 5-35 parts of butyl acrylate, 3-10 parts of methyl methacrylate, 3-20 parts of melamine, 3-20 parts of styrene, 0.03-0.05 parts of vinyl sulfone, 0.15-0.35 parts of 20wt% ammonia water, 3-20 parts of 2,4-methyl-3-cyclohexene carboxaldehyde, 3-10 parts of methacrylic acid, 7.5-12 parts of ammonium polyphosphate, 7.5-12 parts of glycidyl methacrylate, 0.04-0.16 parts of emulsifier, 0.5-1.5 parts of initiator, 1.5-3.5 parts of carbon former, 0.2-0.8 parts of rheological additive, 1-3.5 parts of cellulose solvent, 0.8-2 parts of catalyst and 0.005-0.04 parts of defoaming agent.
[0050] As a preferred embodiment, the solid content of the polyacrylamide emulsion is 35wt% to 45wt%, the degree of polymerization of the polyacrylamide particles is 15000 to 25000, the particle size is 50nm to 80nm, the particle size distribution is a single peak narrow distribution, the thickness of the reinforcing transition layer, the thickness of the shell layer and the thickness of the shell surface graft of the first polyacrylamide-based organic / inorganic hybrid nanoparticles and the second polyacrylamide-based organic / inorganic hybrid nanoparticles are 35nm to 45nm, 25nm to 35nm, and 40nm to 120nm, respectively.
[0051] The invention uses two kinds of polyacrylamide-based organic / inorganic hybrid nanoparticles as the main raw materials of the fireproof material. The polyacrylamide particles in the polyacrylamide emulsion have a particle size of 40nm-200nm and a solid content of 15wt%-55wt%. The flexible core layer particle size of the two kinds of polyacrylamide-based organic / inorganic hybrid nanoparticles is 40nm-200nm, and the particle size distribution is a single peak narrow distribution. For the first polyacrylamide-based organic / inorganic hybrid nanoparticles: the reinforcing transition layer material is a cross-linked network structure containing The invention discloses a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer of melamine formaldehyde material, and a reinforcing transition layer with a thickness of 35nm to 45nm; a shell material of a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silicon dioxide particles with a particle size of 20nm to 30nm, and a shell thickness of 25nm to 35nm; and a shell surface graft of linear ammonium polyphosphate, and a shell surface graft thickness of 40nm to 120nm. For the second polyacrylamide-based organic / inorganic hybrid nanoparticles: the reinforcing transition layer material is a first shell layer of a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer containing a melamine formaldehyde material having a cross-linked network structure, and the reinforcing transition layer thickness is 20nm to 30nm; the shell material is a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm, and the shell thickness is 25nm to 35nm; and the shell surface graft is a linear poly(glycidyl methacrylate polymer, and the shell surface graft thickness is 40nm to 120nm. The two polyacrylamide-based organic / inorganic hybrid nanoparticles are narrow distribution particles. The present invention has the characteristics of multiple cross-linking system, low viscosity of pre-reaction liquid, good impact resistance of coating and water washing resistance. At the same time, the low-temperature use temperature can reach -35°C±1°C, the coating is resistant to ultraviolet radiation for more than 2000 hours, and the flame retardant grade meets the B1 low flammability material standard specified in DIN4102 (German standard) and UL94-V0 high flame retardant material standard (American Insurance Association standard).
[0052] The reason why the organic / inorganic hybrid nanomaterial itself is resistant to low temperature, ultraviolet radiation, impact and water washing is:
[0053] 1. The specially designed multi-layer core-shell structure and preparation process optimize the effective cross-linking between particles, reduce the swelling degree of multi-layer core-shell latex particles and film layers, such as solvents in the system and moisture in the use environment, further improve the density of particles in the film forming process, and reduce the moisture content in the film layer on the basis of improving the strength of the film polymer. Accordingly, it avoids the destruction of the internal structure of the film layer by ice crystals at low temperatures;
[0054] 2. The multiple cross-linking system also increases the film's resistance to ultraviolet radiation;
[0055] 3. Silica particles with double bonds and amine groups are polymerized in the two functional shell layers respectively, so that the "thorn pear"-shaped linear ammonium polyphosphate and polymethacrylic acid molecular chains are evenly distributed on the outer surface of the two latex particles. With the high hardness of the inorganic silica particles, the advantages of the latex particles "soft core and hard shell" are realized. The soft core can ensure that the coating has excellent impact resistance, and the cross-linked organic\inorganic composite hard shell gives the coating scratch resistance and improves the coating's resistance to ultraviolet radiation.
[0056] 4. The "sea buckthorn"-like structure increases the entanglement between the film layer and the cellulose on the glass surface. At the same time, the multiple network cross-linked structures firmly fix these entanglements together, improving the adhesion of the coating. At the same time, this "sea buckthorn"-like structure can give the coating a "lotus effect", further improving the coating's resistance to water washing.
[0057] The fireproof pre-reaction liquid of the present invention exists in the form of a dispersion liquid, and the mass concentration of the dispersion liquid is 40%-60%.
[0058] As a preferred embodiment, the emulsifier is at least one of reactive emulsifiers (such as nonylphenol allyl polyoxyethylene ether ammonium sulfate, allyloxydecyl polyoxyethylene ether ammonium sulfate, etc.); the initiator is at least one of thermal initiators (such as dibenzoyl peroxide, azobisisobutyronitrile, etc.) and redox initiators (such as ammonium persulfate and sodium bisulfite, etc.); the alkenyl silane coupling agent is at least one of vinyl triperoxide tert-butyl silane, vinyl triethoxysilane, butadienyl triethoxysilane, vinyl trimethoxysilane, isobutylenyl triethoxysilane, and vinyl tri(β-methoxyethoxy) silane; the amino silane coupling agent is at least one of one or more silanes selected from phenylaminomethyl triethoxysilane, γ-aminopropyl trimethoxysilane, N-β (aminoethyl)-γ-aminopropyl triethoxysilane, and 3-aminopropyl triethoxysilane; the carbon-forming agent is sucrose, fructose, glucose, or the like. The invention relates to a material comprising at least one of glucose and maltose compounded with pentaerythritol; the rheological additive is at least one of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the cellulose solvent is at least one of dipropylene glycol methyl ether and N-methyl morpholine oxide solution; the pigment is at least one of organic pigment and inorganic pigment; the pigment auxiliary agent is at least one of N-methyl pyrrolidone, N-ethyl pyrrolidone, Nd butyl pyrrolidone and N-octyl pyrrolidone; the catalyst is at least one of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite compounded with dilute hydrochloric acid solution (≤20wt%); the defoamer is at least one of polysiloxane defoamers (such as BYK024 and BYK088) and polyether defoamers (such as GP type glycerol polyether, GPE type polyoxyethylene (polyoxypropylene) ether and PPG type polypropylene glycol).
[0059] The functions of the raw materials used in the fire-proof pre-reaction liquid of the present invention are as follows:
[0060] Two types of polyacrylamide-based organic / inorganic hybrid nanoparticles are mixed with a solvent to form a fire-retardant pre-reaction liquid of polyacrylamide-based organic / inorganic hybrid latex particles with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking. After the fire-retardant pre-reaction liquid comes into contact with transparent cellulose-modified soda-lime glass, it can penetrate into the multiple cross-linking network to form physical cross-links, thereby further entangled with the cellulose on the glass surface and increasing the cross-linking degree of the coating; at the same time, this "sea buckthorn"-shaped structure can give the coating a "lotus effect", further improving the coating's resistance to water washing.
[0061] The two polyacrylamide-based organic / inorganic hybrid nanoparticles used in the embodiments of the present invention are of a core-shell structure, which means that two or more monomers are polymerized in stages or multiple stages under certain conditions, so that different components are enriched on the inside or outside of the particles, i.e., core-shell particles, thereby giving the core and the shell different functions and obtaining particles with excellent performance; wherein the flexible core layer material is polyacrylamide particles and their agglomerates. For the first polyacrylamide-based organic / inorganic hybrid nanoparticles: the reinforcing transition layer material is a first shell layer of a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer containing a melamine formaldehyde material having a cross-linked network structure, the functional shell material is a second shell layer of a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm, and the shell surface graft is linear ammonium polyphosphate; for the second polyacrylamide-based organic / inorganic hybrid nanoparticles: the reinforcing transition layer material is a first shell layer of a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer containing a melamine formaldehyde material having a cross-linked network structure, the functional shell material is a second shell layer of a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silica particles with a particle size of 20nm to 30nm, and the shell surface graft is a linear poly(glycidyl methacrylate) copolymer. This specially designed multi-layer core-shell structure and preparation process optimizes the effective cross-linking between particles themselves and particles, reduces the swelling degree of multi-layer core-shell latex particles and film layers such as solvents in the system and moisture in the use environment, further improves the density of particles in the film forming process, reduces the moisture content in the film layer on the basis of improving the strength of the film polymer, and accordingly avoids the destruction of the internal structure of the film layer by ice crystals at low temperatures; the multiple cross-linking system also increases the film's resistance to ultraviolet radiation; at the same time, silica particles with double bonds and amine groups are polymerized in the functional shell layer to achieve uniform distribution of "sea buckthorn"-shaped linear ammonium polyphosphate and polymethacrylic acid molecular chains on the outer surface of the latex particles, and with the help of the high hardness of silica inorganic particles, the advantage of "soft core and hard shell" of latex particles is achieved. The soft core can ensure that the coating has excellent impact resistance, and the organic\inorganic composite hard shell with a cross-linked structure gives the coating scratch resistance, and can also improve the coating's hardness and ultraviolet radiation resistance.
[0062] The above two polyacrylamide-based organic / inorganic hybrid nanoparticles are narrowly distributed nanoparticles with a particle size of 140nm-400nm. The study found that: based on the principle of "particle design", the fire-retardant pre-reaction liquid composed of multi-layer core-shell structure and low-viscosity polyacrylamide-based organic / inorganic hybrid nanoparticles has shear-thinning characteristics because the entanglement between the outermost layer of branched polymers is only physical entanglement. Through the optimization of other additives, the addition of other additives does not affect the shear-thinning characteristics of the system. Therefore, the prepared fire-retardant pre-reaction liquid also has shear-thinning characteristics.
[0063] Since the two polyacrylamide-based organic / inorganic hybrid nanoparticles are narrowly distributed nanoparticles, they have multiple cross-linking systems, low pre-reaction liquid viscosity, good coating impact resistance, and water washing resistance. At the same time, the low-temperature use temperature can reach -25℃±1℃, the coating UV irradiation time exceeds 2000 hours, and the flame retardant grade meets the B1 low flammability material standard (German standard) specified in DIN4102 and the UL94-V0 high flame retardant material standard (American Insurance Association standard). The above two polyacrylamide-based organic / inorganic hybrid nanoparticles provide reaction sites for the two outermost linear polymers (ammonium polyphosphate and poly(glycidyl methacrylate)) to be grafted onto the core-shell polymer surface by introducing double bonds (alkenyl silane coupling agent) and amine groups (amino silane coupling agent) on the hydrophilic silica surface: the amine groups in the functional shell polymer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle can graft ammonium polyphosphate onto the shell surface through ion exchange reaction in ethanol solution to obtain linear grafted ammonium polyphosphate; at the same time, the second polyacrylamide-based The olefin groups in the functional shell of the organic / inorganic hybrid nanoparticles can undergo polymerization reaction with glycidyl methacrylate to form linear polyglycidyl methacrylate polymers, which provide precursors for the subsequent ring-opening and curing of the epoxy groups with ionic reaction activity, thereby forming materials with multiple network structures. The use of cellulose-based substances as rheological additives in the fire-retardant pre-reaction liquid can improve the leveling properties of the system during painting, and at the same time can penetrate into multiple cross-linked networks to form physical cross-links, thereby further entangled with the cellulose on the surface of the transparent cellulose-modified soda-lime glass for construction, thereby increasing the degree of cross-linking of the coating.
[0064] It should be emphasized that in the fireproof pre-reaction liquid of the present invention, the nano core-shell structured organic-inorganic hybrid particles themselves have the properties of resistance to low temperature, resistance to ultraviolet radiation, resistance to impact, and resistance to water washing.
[0065] The fireproof pre-reaction liquid containing two polyacrylamide-based organic / inorganic hybrid nanoparticles with a "roxburghii"-shaped multi-layer core-shell structure is prepared by the following steps:
[0066] Mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm;
[0067] Put the silica seed solution, aminosilane coupling agent and ethanol into a high-pressure homogenizer according to 10-25:0:0.1-0.5:0.001-0.02 for circulation dispersion for 10 minutes, put it into a three-necked flask, put the three-necked flask into a water bath at 70°C-90°C, stir and disperse at a stirring speed of 100-150r / min for 30 minutes, and then cool to 20°C to obtain a silica dispersion with amino groups on the surface;
[0068] Put the silica seed solution, alkenyl silane coupling agent and ethanol into a high-pressure homogenizer according to 10-25: 0.1-1: 0.001-0.02 for circulation dispersion for 10 minutes, put it into a three-necked flask, and then put the three-necked flask into a water bath pot at 70°C-90°C, stir and disperse at a stirring speed of 100-150r / min for 30 minutes, and then cool to 20°C to obtain a silica dispersion with double bonds on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11);
[0069] Butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt% ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and reactive emulsifier are mixed in the weight proportion of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution; 0.5-80 weight parts of the first mixed solution, 6-12 weight parts of deionized water and 0.005-1 weight part of initiator are added dropwise to 20-150 weight parts of a granular material with a particle size of 0.1-0.03 mm at a temperature of 60-65° C. by means of a starvation polymerization method; In a polyacrylamide emulsion with a diameter of 40nm to 200nm and a solid content of 15wt% to 55wt%, after polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion with a cross-linked core-shell structure; butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier are mixed in weight parts of 0.1 to 6:0.1 to 6:0.1 to 6:0.01 to 0.02 to obtain a second mixed solution; by means of a starvation polymerization method, at a temperature of 60 to 65°C and at a constant temperature of 100 to 200°C, 0.1-18 weight parts of the second mixed solution, 15-40 weight parts of deionized water, 10-26 weight parts of a silicon dioxide dispersion with amino groups on the surface, and 0.003-0.03 weight parts of an initiator are added dropwise at a constant speed to 26-243 weight parts of the first polymer template latex. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material embedded with silicon dioxide particles with an amino group and a particle size of 20nm-30nm is coated on the surface of the polyacrylamide latex particles to obtain a second polymer template latex with a bayberry-like multilayer core-shell structure; preparing a first polyacrylamide-based organic / Emulsion of inorganic hybrid nanoparticles: by means of ion exchange reaction, 7 to 26 parts by weight of the third mixed solution are added dropwise to 51 to 327 parts by weight of the second polymer template emulsion at a constant speed at a temperature of 30 to 40°C, stirred at a stirring speed lower than 80r / min, and refluxed and condensed for 4 hours under this temperature condition to form a polymer with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles, thereby obtaining an emulsion containing first polyacrylamide-based organic / inorganic hybrid nanoparticles; furthermore, first polyacrylamide-based organic / inorganic hybrid nanoparticles having a "sea buckthorn"-shaped multilayer core-shell structure and capable of multiple crosslinking can be obtained.
[0070] By means of starvation polymerization, 0.1 to 18 parts by weight of a second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silicon dioxide dispersion with double bonds on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 242 parts by weight of a first polymer template latex at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material embedded with silicon dioxide particles with a particle size of 20 nm to 30 nm and double bonds is coated on the surface of the polyacrylamide latex particles to obtain a third polymer template latex with a multilayer core-shell structure; A fourth mixed solution is prepared according to the weight ratio of glycidyl methacrylate, initiator and deionized water of 5-15:0.01-0.2:5-10; 10-25 weight parts of the fourth mixed solution are added dropwise to 51-327 weight parts of the third polymer template latex at a constant speed under a temperature condition of 60-65°C, stirred at a stirring speed lower than 80r / min, and refluxed and condensed for 3 hours under this temperature condition to form a second polymer with linear polymethacrylate glycidyl as a branch on the surface of the latex particles, and obtain second polyacrylamide-based organic / inorganic hybrid nanoparticles with a "sea buckthorn"-shaped multi-layer core-shell structure and multiple cross-linking.
[0071] The carbonizing agent, the rheological additive and the deionized water are mixed in a weight ratio of 1-5:0.1-1:10-25, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and aged for 12 hours to obtain a transparent and dynamically reversible gel material;
[0072] A first polyacrylamide-based organic / inorganic hybrid nanoparticle, a second polyacrylamide-based organic / inorganic hybrid nanoparticle, a cellulose solvent, a catalyst and deionized water are mixed in a weight ratio of 58-353:61-352:0.5-4:0.5-2.5:10-30 to obtain a first fireproof mixed liquid, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; 11-30 parts by weight of a gelling material are added to the first fireproof mixed liquid, and stirred at a stirring speed of less than 80 r / min for 80 minutes at room temperature to obtain a clear or slightly turbid second fireproof mixed liquid; 0.5-2.5 parts by weight of a catalyst and 0.001-0.05 parts by weight of a defoaming agent are added to the second fireproof mixed liquid in sequence, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fireproof pre-reaction liquid, which is left to stand for use;
[0073] In accordance with the standard requirements of XF 159-2011 "Water-based flame retardants", the fire-retardant pre-reaction liquid is sprayed onto the surface of the transparent cellulose-modified soda-lime glass product, left to stand for 50 minutes, and then placed in a 50°C oven for 4 hours after the surface of the glass product is dry, and then heated to 80°C and baked for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure.
[0074] Furthermore, in the above steps, the particle size of the polyacrylamide particles in the polyacrylamide emulsion is 40nm-200nm, the solid content is 15wt%-55wt%, the flexible core layer particle size of the two polyacrylamide-based organic / inorganic hybrid nanoparticles is 40nm-200nm, and the particle size distribution is also a single peak narrow distribution; the reinforcing transition layer material of the two polyacrylamide-based organic / inorganic hybrid nanoparticles is a first shell layer of a poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) copolymer containing a melamine formaldehyde material having a cross-linked network structure, and the functional shell material is a poly(butyl acrylate-methyl methacrylate-methacrylic acid) copolymer inlaid with silicon dioxide particles with a particle size of 20nm-30nm, and the shell thickness is 25nm-35nm; the shell surface graft material is a linear ammonium polyphosphate or a linear poly(glycidyl methacrylate) polymer, and the shell surface graft thickness is 40nm-120nm. The two polyacrylamide-based organic / inorganic hybrid nanoparticles are narrow distribution particles.
[0075] Furthermore, in the above step S16), the stirring time is 20 to 60 minutes, preferably 40 minutes.
[0076] When preparing the fireproof pre-reaction liquid in the embodiment of the present invention, firstly, tetraethyl orthosilicate, 20% ammonia water and deionized water are mixed, and the mixture is allowed to stand for aging to obtain a silicon dioxide seed solution; the silicon dioxide seed solution, an amino silane coupling agent and ethanol are homogenized and dispersed at high pressure, and the stirring reaction is continued at a stirring speed of less than 150 r / min to obtain a silicon dioxide dispersion liquid with an amino group on the surface; the silicon dioxide seed solution, an alkenyl silane coupling agent and ethanol are homogenized and dispersed at high pressure, and the stirring reaction is continued at a stirring speed of less than 150 r / min to obtain a silicon dioxide dispersion liquid with an alkenyl group on the surface; butyl acrylate, melamine, styrene, divinyl sulfone and 20wt% ammonia water are mixed, and the mixture is allowed to stand for aging to obtain a silicon dioxide seed solution; the silicon dioxide seed solution, an amino silane coupling agent and ethanol are homogenized and dispersed at high pressure, and the stirring reaction is continued at a stirring speed of less than 150 r / min to obtain a silicon dioxide dispersion liquid with an alkenyl group on the surface; the silicon dioxide seed solution ... , 2,4-methyl-3-cyclohexene carboxaldehyde and a reactive emulsifier are mixed to obtain a first mixed solution; by means of starvation polymerization, the first mixed solution, deionized water and an initiator are added dropwise to a polyacrylamide emulsion to obtain a first polymer template emulsion having a cross-linked core-shell structure; butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier are mixed to obtain a second mixed solution; by means of starvation polymerization, the second mixed solution, deionized water, a silica dispersion with amino groups on the surface and an initiator are added dropwise to the first polymer template emulsion to obtain a second polymer template emulsion having a multilayer core-shell structure; ammonium polyphosphate, ethanol and deionized water are mixed to obtain a third mixed solution ; By means of ion exchange reaction, the third mixed solution is added dropwise to the second polymer template emulsion, and reflux condensation reaction is carried out to obtain a polymer emulsion containing a first polyacrylamide-based organic / inorganic multilayer core-shell structure with a "roxburgh" shape, linear ammonium polyphosphate as the outermost branch chain, and multiple crosslinks; the second mixed solution, ionized water, a silica dispersion with double bonds on the surface, and an initiator are added dropwise to the first polymer template emulsion to obtain a third polymer template emulsion with a multilayer core-shell structure; glycidyl methacrylate, an initiator, and deionized water are mixed to obtain a fourth mixed solution; the fourth mixed solution is added dropwise to the third polymer template emulsion at a constant speed, and reflux condensation reaction is carried out , obtaining a polymer emulsion containing a second polyacrylamide-based organic / inorganic multilayer core-shell structure having a "roxburgh" shape, with a linear poly(glycidyl methacrylate) polymer as the outermost branch chain, and being multiply crosslinkable; mixing a carbon-forming agent, a rheological additive, and deionized water, stirring at a stirring speed of less than 100 r / min, and standing for aging to obtain a gel material; mixing acrylamide-based organic / inorganic hybrid nanoparticles having a "roxburgh"-shaped multilayer core-shell structure and being multiply crosslinkable, a cellulose solvent, a catalyst, and deionized water, stirring at a stirring speed of less than 80 r / min, and then adding the gel material thereto, stirring at a stirring speed of less than 80 r / min to obtain a pre-reaction liquid;Catalyst and defoamer are added to the pre-reaction liquid in sequence, and stirred at a stirring speed of less than 80r / min to obtain the fire-proof pre-reaction liquid on the surface of the transparent cellulose modified soda-lime glass product. The fire-proof pre-reaction liquid is sprayed on the surface of the transparent cellulose modified soda-lime glass product, and the surface of the glass product is baked after the surface is dried, so that the cellulose on the glass surface and the fire-proof pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure, thereby improving the flame retardant performance of the product. ;
[0077] The fireproof material formed after the fireproof pre-reaction liquid provided by the embodiment of the present invention reacts is an intumescent flame retardant system. When encountering a fire, the ammonium polyphosphate on the surface of the glass cellulose is thermally decomposed to generate phosphoric acid and pyrophosphoric acid with strong dehydration effect, so that the carbon forming agent is esterified, and then dehydrated and carbonized. The water vapor formed by the reaction and the ammonia decomposed in the melamine formaldehyde resin can also expand the carbon layer, and finally form a multi-porous carbon layer, thereby isolating air and heat conduction, protecting glass products, and achieving the purpose of flame retardancy. At the same time, the fireproof material formed after the fireproof pre-reaction liquid provided by the embodiment of the present invention reacts has the following advantages: good thermal stability, and the multiple cross-linking system ensures that the coating can withstand high temperature reprocessing above 150°C after low-temperature baking; when a fire suddenly occurs, a large amount of volatile substances can be released, blocking oxygen, and expanding and foaming at the same time; this "thorn pear"-shaped multi-layer core-shell structure and multi-crosslinkable fireproof structure can be evenly distributed on the surface of the wood fiber during the film forming process, and can form a layer of expanded carbon that completely covers the surface of the material in the fire to prevent it from dripping and spreading the fire.
[0078] As a preferred embodiment, the thickness of the fireproof layer is 0.02-0.3 mm.
[0079] The present invention can control the thickness of the fireproof layer formed by the fireproof pre-reaction liquid on the glass surface to 0.02-0.3mm, and manufacture a thinner fireproof layer under the premise of ensuring fireproof performance, reduce the production cost of the window, and expand the application scope of the fireproof material. The fireproof material formed by the fireproof pre-reaction liquid of the embodiment of the present invention will expand to form a porous heat-insulating layer after encountering fire, and the thickness of the expansion layer is about 15 to 20 times the thickness of the original fireproof layer, and gradually forms a heat-insulating layer of about 1mm to 4mm; if the thickness of the fireproof material is less than 0.02mm, the fireproof layer is too thin, and the formed heat-insulating layer cannot isolate the heat transfer within a certain period of time, resulting in the overall fireproof time being lower than the design value; if the thickness of the fireproof material is greater than 0.3mm, the fireproof layer is too thick, which will cause the excess fireproof pre-reaction liquid on the glass surface to be unable to continue to form an effective network entanglement with cellulose, and also block the volatilization of the solution inside the coating, so that the early baking time is greatly increased, the cost is too high, and the fireproof performance is reduced.
[0080] The present invention is further described below with reference to specific embodiments, but is not intended to limit the present invention.
[0081] The reagents used in the embodiments of the present invention are all commercially available products.
[0082] Example 1
[0083] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0084] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0085] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0086] Since the particle size of the latex particles in the polyacrylamide emulsion is narrowly distributed, the particle size of the two polyacrylamide-based organic / inorganic hybrid nanoparticles is also unimodal, and similarly, the particle size of the flexible core layer particles and the two polyacrylamide-based organic / inorganic hybrid nanoparticles in the following examples is also narrowly distributed;
[0087] (2) Prepare a fire-proof pre-reaction liquid by the following steps:
[0088] 2.3 kg of tetraethyl orthosilicate, 0.03 kg of concentrated ammonia water with a concentration of 25 wt%, and 15 kg of deionized water were mixed and allowed to stand for 36 hours to generate a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, and the particle size of the silicon dioxide particles was 20 nm to 30 nm;
[0089] 12.5 kg of silica seed solution, 0.3 kg of amino silane coupling agent and 0.01 kg of ethanol were placed in a high-pressure homogenizer for circulation dispersion for 10 minutes, and then placed in a three-necked flask, and then the three-necked flask was placed in a water bath at 70°C to 90°C, stirred and dispersed at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooled to 20°C to obtain a silica dispersion with amino groups on the surface;
[0090] 12.5 kg of silica seed solution, 0.3 kg of alkenyl silane coupling agent and 0.01 kg of ethanol were placed in a high-pressure homogenizer for circulation dispersion for 10 minutes, and then placed in a three-necked flask, and then the three-necked flask was placed in a water bath at 70°C to 90°C, stirred and dispersed at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooled to 20°C to obtain a silica dispersion with double bonds on the surface;
[0091] 5kg of butyl acrylate, 3kg of melamine, 3kg of styrene, 0.02kg of divinyl sulfone, 0.1kg of 20wt% ammonia water, 4kg of 2,4-methyl-3-cyclohexene carboxaldehyde, and 0.04kg of emulsifier are mixed to prepare a first mixed solution; by means of starvation polymerization, 15.16kg of the first mixed solution, 7.5kg of deionized water, and 0.05kg of initiator are added dropwise to 40kg of polyacrylamide emulsion with a particle size of 40nm-200nm and a solid content of 15wt%-55wt% at a constant speed under a temperature condition of 60-65°C; after the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material embedded with silicon dioxide particles with a particle size of 20nm-30nm is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion with a cross-linked core-shell structure;
[0092] 2kg of butyl acrylate, 2kg of methyl methacrylate, 2kg of methacrylic acid, and 0.015kg of an emulsifier are used to prepare a second mixed solution; 6.015kg of the second mixed solution, 20kg of deionized water, 12.81kg of a silicon dioxide dispersion with amino groups on the surface, and 0.02kg of an initiator are added dropwise to 62.71kg of a first polymer template latex at a constant speed under a temperature condition of 60-65°C by means of a starvation polymerization method; after the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silicon dioxide particles with amino groups having a particle size of 20nm-30nm is coated on the surface of the polyacrylamide latex particles, thereby obtaining a second polymer template latex having a bayberry-like multilayer core-shell structure;
[0093] A third mixed solution is prepared by using 10 kg of ammonium polyphosphate, 0.7 kg of ethanol and 5 kg of deionized water; by means of ion exchange reaction, 15.7 kg of the third mixed solution is added dropwise to 101.555 kg of the second polymer template latex at a constant speed under a temperature condition of 30 to 40° C., stirred at a stirring speed lower than 80 r / min, and refluxed and condensed for 4 hours under this temperature condition to form a first polymer latex with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles; and a first polyacrylamide-based organic / inorganic hybrid nanoparticle having a "roxburghii"-shaped multi-layer core-shell structure and capable of multiple crosslinking is obtained;
[0094] By means of starvation polymerization, 6.015 kg of the second mixed solution, 20 kg of deionized water, 12.81 kg of silica dispersion with double bonds on the surface, and 0.02 kg of initiator are added dropwise to 62.71 kg of the first polymer template latex at a constant speed under a temperature condition of 60-65° C. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material embedded with silica particles with a particle size of 20 nm to 30 nm and double bonds is coated on the surface of the polyacrylamide latex particles, thereby obtaining a third polymer template latex having a bayberry-like multilayer core-shell structure;
[0095] A fourth mixed solution was prepared by adding 10 kg of glycidyl methacrylate, 0.15 kg of initiator and 7.5 kg of deionized water; by means of starvation polymerization, 17.65 kg of the fourth mixed solution was added dropwise to 101.555 parts by weight of the third polymer template latex at a constant speed under a temperature condition of 60-65°C, stirred at a stirring speed lower than 80 r / min, and refluxed and condensed under this temperature condition for 4 hours to form a first polymer latex with a linear poly(glycidyl methacrylate) polymer as the outermost branch chain on the surface of the latex particles; and a second polyacrylamide-based organic / inorganic hybrid nanoparticle having a "sea buckthorn"-shaped multi-layer core-shell structure and capable of multiple crosslinking was obtained.
[0096] 3 kg of carbonizing agent, 0.5 kg of rheological additive and 20 kg of deionized water were mixed, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and then aged for 12 hours to obtain a transparent, dynamically reversible gel material;
[0097] 117.255 kg of the first polyacrylamide-based organic / inorganic hybrid nanoparticles, 119.205 kg of the second polyacrylamide-based organic / inorganic hybrid nanoparticles, and 3 kg of cellulose solvent are stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to form a uniform suspension; 23.5 kg of a transparent, dynamically reversible gelling material is added thereto, and stirred at a stirring speed of less than 100 r / min for 60 minutes at room temperature to obtain a clear or slightly turbid pre-reaction liquid; 1.5 kg of a catalyst and 0.02 kg of a defoaming agent are added to the pre-reaction liquid in sequence, and stirred at a stirring speed of less than 80 r / min for 40 minutes at room temperature to obtain a fire-proof pre-reaction liquid for the surface of wooden products for railway vehicles, which is left to stand for use;
[0098] In accordance with the standard requirements of XF 159-2011 "Water-based flame retardants", the fire-retardant pre-reaction liquid is sprayed onto the surface of the transparent cellulose-modified soda-lime glass product, left to stand for 50 minutes, and after the surface of the glass product is dry, it is placed in a 50°C oven and baked for 4 hours, and then heated to 80°C and baked for 3 hours, so that the cellulose on the glass surface and the fire-retardant pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure, thereby improving the flame retardant properties of the product.
[0099] Example 2
[0100] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0101] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0102] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 5.5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 7.5kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0103] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0104] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0105] Example 3
[0106] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0107] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0108] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 7kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0109] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0110] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0111] Example 4
[0112] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0113] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0114] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 4.5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 6.5kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0115] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0116] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0117] Example 5
[0118] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0119] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0120] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 4kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 6kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0121] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0122] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0123] Example 6
[0124] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0125] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0126] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6.5kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8.5kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0127] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0128] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0129] Example 7
[0130] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0131] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0132] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 2.5kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0133] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0134] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0135] Example 8
[0136] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0137] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0138] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.5kg of rheological additive, 3.5kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0139] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0140] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0141] Example 9
[0142] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0143] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0144] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.04kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.8kg of rheological additive, 3.5kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0145] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0146] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0147] Example 10
[0148] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0149] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0150] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.05kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.8kg of rheological additive, 3.5kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoaming agent.
[0151] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0152] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0153] Embodiment 11
[0154] The fire-proof pre-reaction liquid in this embodiment is prepared by the following steps:
[0155] (1) Weigh the raw materials of the fire-proof pre-reaction liquid according to the following weights:
[0156] 4.6kg of tetraethyl orthosilicate, 0.06kg of concentrated ammonia water with a concentration of 25wt%, 117.5kg of deionized water, 0.3kg of alkenyl silane coupling agent, 0.3kg of amino silane coupling agent, 0.72kg of ethanol, 80kg of polyacrylamide solution, 14kg of butyl acrylate, 4kg of methyl methacrylate, 6kg of melamine, 6kg of styrene, 0.03kg of divinyl sulfone, 0.2kg of ammonia water with a concentration of 20wt%, 8kg of 2,4-methyl-3-cyclohexene carboxaldehyde, 4kg of methacrylic acid, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.38kg of emulsifier, 0.65kg of initiator, 3kg of carbonizing agent, 0.8kg of rheological additive, 3.5kg of cellulose solvent, 1.5kg of catalyst, and 0.02kg of defoamer.
[0157] (2) The above raw materials are used to prepare a fire-retardant pre-reaction liquid according to the same preparation method as Example 1.
[0158] The method for preparing the fire-proof pre-reaction liquid in this embodiment is the same as the method for preparing the fire-proof pre-reaction liquid in Embodiment 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0159] Comparative Example 1
[0160] This comparative example provides a fire-proof pre-reaction liquid, the raw materials of which are 55kg deionized water, 3kg melamine, 4kg 2,4-methyl-3-cyclohexene carboxaldehyde, 10kg ammonium polyphosphate, 10kg glycidyl methacrylate, 0.05kg initiator, 3kg carbonizing agent, 0.5kg rheological additive, 3kg cellulose solvent, 1.5kg catalyst, and 0.02kg defoamer. The preparation method of the fire-proof pre-reaction liquid in this comparative example is the same as the preparation method of the fire-proof pre-reaction liquid in Example 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0161] Comparative Example 2
[0162] This comparative example provides a fire-proof pre-reaction liquid, whose raw materials are 55kg of deionized water, 3kg of melamine, 4kg of 2,4-methyl-3-cyclohexene formaldehyde, 10kg of ammonium polyphosphate, 10kg of glycidyl methacrylate, 0.05kg of initiator, 1.5kg of catalyst, and 0.02kg of defoamer.
[0163] The preparation method of the fire-proof pre-reaction liquid in this comparative example is the same as the preparation method of the fire-proof pre-reaction liquid in Example 1, except that the composition of the fire-proof pre-reaction liquid is different.
[0164] Comparative Example 3
[0165] This comparative example is a transparent cellulose-modified soda-lime glass product that has not been flame-retardant treated.
[0166] According to the standard requirements of XF 159-2011 "Water-based Flame Retardant", the flame retardant performance test was conducted on the glass samples coated with the fire-retardant pre-reaction liquid provided in Examples 1 to 12 and Comparative Examples 1 to 3. Four parallel samples were taken in the experiment, and the average value of the data was taken as the experimental result; the viscosity of the fire-retardant pre-reaction liquid was measured according to the GB / T1723 coating viscosity determination method; and the apparent quality of each wooden product was obtained by naked eye observation. The performance parameters of the fire-retardant pre-reaction liquid prepared in the examples of the present invention and the comparative examples are shown in Table 1.
[0167] Table 1 Performance parameters of fire retardant pre-reaction liquid
[0168]
[0169] As can be seen from Table 1, the fireproof pre-reaction liquid in the present invention has a long fireproof time and water-resistant after solidification, while the fireproof layer formed by the fireproof pre-reaction liquid prepared in the comparative example does not have the characteristics of water-resistant; the fireproof time formed by the fireproof pre-reaction liquid in the present invention after solidification is 1.5-7 times that of the comparative example, and the hardness and ultraviolet radiation resistance time are also significantly higher than those of the comparative example. The above description uses only 2,4-methyl-3-cyclohexene melamine formaldehyde resin and ammonium polyphosphate as fireproof materials, which are easily washed away during water flushing, seriously affecting the safety of glass windows. The present invention improves the formula of the fireproof pre-reaction liquid, adopts polyacrylamide-based organic / inorganic hybrid latex particles with a "thorn pear"-shaped multi-layer core-shell structure and a multi-crosslinkable core-shell structure and is mixed with an additive, and a synergistic effect is generated between the components of the fireproof pre-reaction liquid, thereby improving the flame retardant properties of the material, especially after water flushing, the flame retardant properties of the glass product are still unaffected, and at the same time, the low temperature resistance of the fireproof layer formed after the fireproof pre-reaction liquid is cured is also improved, and it can be used in low temperature (-25℃±1℃) and outdoor environment. The fireproof pre-reaction liquid prepared by the embodiment of the present invention has the advantages of low viscosity, high hardness, good adhesion, long flame retardant time, resistance to low temperature and resistance to ultraviolet radiation, and can form a transparent coating when applied to the surface of an object.
[0170] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.
[0171] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. Organic / inorganic hybrid nanomaterials, characterized in that: The invention comprises a first polyacrylamide-based organic / inorganic hybrid nanoparticle and a second polyacrylamide-based organic / inorganic hybrid nanoparticle, wherein the first polyacrylamide-based organic / inorganic hybrid nanoparticle and the second polyacrylamide-based organic / inorganic hybrid nanoparticle both comprise a flexible core layer, a shell layer and a reinforcing transition layer, wherein the reinforcing transition layer is arranged between the flexible core layer and the shell layer; wherein the shell layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle is a polymer layer of a phosphorus-containing polymer and the surface of the shell layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle is grafted with linear ammonium polyphosphate, the shell layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticle is a polymer layer containing an epoxy polymer and the second polyacrylamide-based organic / inorganic hybrid nanoparticle is a polymer layer containing an epoxy polymer and the surface of the second polyacrylamide-based organic / inorganic hybrid nanoparticle is grafted with linear ammonium polyphosphate, The surface of the shell layer is grafted with linear poly(glycidyl methacrylate); the flexible core layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle and the flexible core layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticle are both polyacrylamide latex particles; the reinforcing transition layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle and the reinforcing transition layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticle are both polymer layers containing melamine formaldehyde material with a cross-linked network structure; the polymer in the shell layer of the first polyacrylamide-based organic / inorganic hybrid nanoparticle and the polymer in the shell layer of the second polyacrylamide-based organic / inorganic hybrid nanoparticle both contain at least one polymer that can form an interpenetrating network structure with cellulose; The material composed of the first polyacrylamide-based organic / inorganic hybrid nanoparticles is made of the following components: 7 to 26 parts by weight of a third mixed solution and 51 to 327 parts by weight of a second polymer template emulsion; the third mixed solution is mixed with 5 to 15 parts by weight of ammonium polyphosphate, 0.1 to 1 parts by weight of ethanol and 2 to 10 parts by weight of deionized water; the second polymer template emulsion is made of 0.1 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silicon dioxide dispersion with amino groups on the surface, 0.003 to 0.03 parts by weight of an initiator and 26 to 243 parts by weight of the first polymer template emulsion; the second mixed solution is mixed with 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid and 0.01 to 0.02 parts by weight of a reactive emulsifier; The first polymer template emulsion is prepared from 0.5 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water, 0.005 to 1 parts by weight of an initiator, and 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt%; the first mixed solution is prepared from 0.1 to 20 parts by weight of butyl acrylate, 0.1 to 20 parts by weight of melamine, 0.1 to 20 parts by weight of styrene, 0.01 to 0.03 parts by weight of divinyl sulfone, 0.05 to 0.2 parts by weight of concentrated A 20wt% ammonia water, 0.1-20 weight parts of 2,4-methyl-3-cyclohexene carboxaldehyde and 0.002-0.08 weight parts of a reactive emulsifier are mixed; a hydrophilic silica dispersion with amino groups on the surface is made of 10-25 weight parts of silica seed solution, 0.1-1 weight parts of amino silane coupling agent and 0.001-0.02 ethanol; a silica seed solution is made of 2-3 weight parts of tetraethyl orthosilicate, 0.02-0.04 weight parts of 25wt% concentrated ammonia water and 8-22 deionized water; The material composed of the second polyacrylamide-based organic / inorganic hybrid nanoparticles is made of the following components: 10 to 25 parts by weight of the fourth mixed solution and 51 to 327 parts by weight of the fourth polymer template emulsion; the fourth mixed solution is mixed with 5 to 15 parts by weight of glycidyl methacrylate, 0.01 to 0.2 parts by weight of initiator and 5 to 10 parts by weight of deionized water; the fourth polymer template emulsion is made of 0.1 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of silica dispersion with double bonds on the surface, 0.003 to 0.03 parts by weight of initiator and 26 to 243 parts by weight of the first polymer template emulsion; the second mixed solution is mixed with 0.1 to 6 parts by weight of butyl acrylate, 0.1 to 6 parts by weight of methyl methacrylate, 0.1 to 6 parts by weight of methacrylic acid and 0.01 to 0.02 parts by weight of reactive emulsifier; the first polymer template emulsion is mixed with 0.1 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water, 10 to 26 parts by weight of silica dispersion with double bonds on the surface, 0.003 to 0.03 parts by weight of initiator and 26 to 243 parts by weight of the first polymer template emulsion. The first mixed solution is prepared by mixing 0.1-20 parts by weight of butyl acrylate, 0.1-20 parts by weight of melamine, 0.1-20 parts by weight of styrene, 0.01-0.03 parts by weight of divinyl sulfone, 0.05-0.2 parts by weight of 20wt% ammonia water, 0.1-2 The invention discloses a method for preparing a hydrophilic silica dispersion liquid comprising: a silica seed solution and a silica slurry; a silica seed solution and a silica slurry comprising: a silica slurry comprising: 10 to 25 parts by weight of a silica seed solution, 0.1 to 1 parts by weight of an aminosilane coupling agent, and 0.001 to 0.02 parts by weight of ethanol; and a silica seed solution and a silica slurry comprising: 2 to 3 parts by weight of ethyl orthosilicate, 0.02 to 0.04 parts by weight of concentrated ammonia water with a concentration of 25 wt %, and 8 to 22 parts of deionized water.
2. The organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The organic / inorganic hybrid nanomaterial is characterized in that the polymerization degree of the polyacrylamide particles in the polyacrylamide emulsion is 10000-100000, the particle size is 40nm-200nm, and the particle size distribution is a single peak narrow distribution.
3. The organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The alkenyl silane coupling agent is one or more of vinyl tert-butyl triperoxide silane, vinyl triethoxy silane, butadienyl triethoxy silane, vinyl trimethoxy silane, isobutylenyl triethoxy silane and vinyl tri(β-methoxyethoxy) silane.
4. The organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The aminosilane coupling agent is one or more of one or more of the group consisting of anilinomethyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltriethoxysilane and 3-aminopropyltriethoxysilane.
5. The organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The initiator is one or both of a thermal initiator and a redox initiator.
6. The method for preparing the organic / inorganic hybrid nanomaterial according to claim 1, characterized in that: The steps include: S11) preparing a silicon dioxide seed solution: mixing tetraethyl orthosilicate, concentrated ammonia water with a concentration of 25 wt % and deionized water in a weight ratio of 2-3:0.02-0.04:8-22, standing and aging for 36 hours, and generating a silicon dioxide seed solution after alcoholysis of tetraethyl orthosilicate, wherein the particle size of the silicon dioxide particles is 20 nm-30 nm; S12-1) preparing a silica dispersion with amine groups on the surface: placing a silica seed solution, an amino-silane coupling agent and ethanol in a weight ratio of 10 to 25: 0.1 to 1: 0.001 to 0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes to obtain a first primary dispersion, placing the first primary dispersion in a three-necked flask, and then placing the three-necked flask in a water bath at 70°C to 90°C, stirring and dispersing at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooling to 20°C to obtain a silica dispersion with amine groups on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11); S12-2) preparing a silica dispersion with double bonds on the surface: placing a silica seed solution, an alkenyl silane coupling agent and ethanol in a weight ratio of 10 to 25: 0.1 to 1: 0.001 to 0.02 in a high-pressure homogenizer for circulation dispersion for 10 minutes to obtain a second primary dispersion, placing the second primary dispersion in a three-necked flask, and then placing the three-necked flask in a water bath at 70°C to 90°C, stirring and dispersing at a stirring speed of 100 to 150 r / min for 30 minutes, and then cooling to 20°C to obtain a silica dispersion with double bonds on the surface; wherein the silica seed solution is the silica seed solution obtained in step S11); S13) preparing a first polymer template emulsion, the specific steps are as follows: S13-1) mixing butyl acrylate, melamine, styrene, divinyl sulfone, 20 wt % ammonia water, 2,4-methyl-3-cyclohexene carboxaldehyde and a reactive emulsifier in a weight ratio of 0.1-20:0.1-20:0.1-20:0.01-0.03:0.05-0.2:0.1-20:0.002-0.08 to prepare a first mixed solution; S13-2) By means of starvation polymerization, 0.5 to 80 parts by weight of the first mixed solution, 6 to 12 parts by weight of deionized water and 0.005 to 1 part by weight of an initiator are added dropwise to 20 to 150 parts by weight of a polyacrylamide emulsion having a particle size of 40 nm to 200 nm and a solid content of 15 wt% to 55 wt% at a constant speed under a temperature condition of 60 to 65° C. After the polymerization is completed, a layer of poly(butyl acrylate-styrene-divinyl sulfone-2,4-methyl-3-cyclohexene melamine formaldehyde) material is coated on the surface of the polyacrylamide latex particles to obtain a first polymer template emulsion having a cross-linked core-shell structure; S14) preparing an emulsion containing first polyacrylamide-based organic / inorganic hybrid nanoparticles, the specific steps are as follows: S14-1) mixing butyl acrylate, methyl methacrylate, methacrylic acid and a reactive emulsifier in a weight ratio of 0.1-6:0.1-6:0.1-6:0.01-0.02 parts to prepare a second mixed solution; S14-2) preparing a second polymer template emulsion: by means of starvation polymerization, at a temperature of 60 to 65° C., 0.1 to 18 parts by weight of a second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having amino groups on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 243 parts by weight of a first polymer template emulsion at a constant speed. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material inlaid with silica particles having an amino group and a particle size of 20 nm to 30 nm is coated on the surface of the polyacrylamide latex particles, thereby obtaining a second polymer template emulsion having a bayberry-like multilayer core-shell structure; S14-3) preparing a third mixed solution: mixing ammonium polyphosphate, ethanol and deionized water in a weight ratio of 5-15:0.5-1:2-10 to prepare a third mixed solution; S14-4) preparing an emulsion containing first polyacrylamide-based organic / inorganic hybrid nanoparticles: by means of an ion exchange reaction, 7 to 26 parts by weight of the third mixed solution are added dropwise to 51 to 327 parts by weight of the second polymer template emulsion at a constant speed at a temperature of 30 to 40° C., stirred at a stirring speed of less than 80 r / min, and refluxed under this temperature for 4 hours to form a polymer with linear ammonium polyphosphate as the outermost branch chain on the surface of the latex particles, thereby obtaining an emulsion containing first polyacrylamide-based organic / inorganic hybrid nanoparticles; S15) preparing an emulsion containing a second polyacrylamide-based organic / inorganic hybrid nanoparticle, the specific steps are as follows: S15-1) preparing a third polymer template emulsion: by means of starvation polymerization, at a temperature of 60 to 65° C., 0.1 to 18 parts by weight of the second mixed solution, 15 to 40 parts by weight of deionized water, 10 to 26 parts by weight of a silica dispersion having double bonds on the surface, and 0.003 to 0.03 parts by weight of an initiator are added dropwise to 26 to 242 parts by weight of the first polymer template emulsion at a constant speed. After the polymerization is completed, a layer of poly(butyl acrylate-methyl methacrylate-methacrylic acid) material embedded with silica particles having a particle size of 20 nm to 30 nm and having double bonds is coated on the surface of the polyacrylamide latex particles, thereby obtaining a third polymer template emulsion having a multilayer core-shell structure; S15-2) preparing a fourth mixed solution: preparing a fourth mixed solution by mixing glycidyl methacrylate, an initiator and deionized water in a weight ratio of 5-15:0.01-0.2:5-10; S15-3) preparing an emulsion containing second polyacrylamide-based organic / inorganic hybrid nanoparticles: adding 10 to 25 parts by weight of the fourth mixed solution to 51 to 327 parts by weight of the third polymer template emulsion at a constant speed at a temperature of 60 to 65° C., stirring at a stirring speed of less than 80 r / min, and reflux condensing for 3 hours at this temperature to form a second polymer with linear polymethacrylate glycidyl ester as a branch on the surface of the latex particles, thereby obtaining an emulsion containing second polyacrylamide-based organic / inorganic hybrid nanoparticles; S16) Compounding the emulsion containing the first polyacrylamide-based organic / inorganic hybrid nanoparticles and the emulsion containing the second polyacrylamide-based organic / inorganic hybrid nanoparticles to obtain an organic / inorganic hybrid nanomaterial.
7. Fire-proof pre-reaction liquid, characterized in that: The invention comprises at least the following components: 58 to 353 parts by weight of a first polyacrylamide-based organic / inorganic hybrid nanoparticle, 61 to 352 parts by weight of a second polyacrylamide-based organic / inorganic hybrid nanoparticle, 0.5 to 4 parts by weight of a cellulose solvent, 0.5 to 2.5 parts by weight of a catalyst and 10 to 30 parts by weight of deionized water; the first polyacrylamide-based organic / inorganic hybrid nanoparticle is the first polyacrylamide-based organic / inorganic hybrid nanoparticle described in claim 1, and the second polyacrylamide-based organic / inorganic hybrid nanoparticle is the second polyacrylamide-based organic / inorganic hybrid nanoparticle described in claim 1.
8. The fire-proof pre-reaction liquid according to claim 7, characterized in that: The invention also comprises: 1 to 5 parts by weight of a carbonizing agent, 0.001 to 0.05 parts by weight of a defoaming agent and 0.1 to 1 parts by weight of a rheological aid; the carbonizing agent is compounded by pentaerythritol and one or more of sucrose, fructose, glucose and maltose; the rheological aid is one or more of hydroxymethyl cellulose, methyl cellulose, ethyl cellulose, hydroxypropyl methyl cellulose and hydroxyethyl cellulose; the antifreeze plasticizer is one or more of ethylene glycol, glycerol and 1,4-butanediol; the cellulose solvent is one or both of dipropylene glycol methyl ether and N-methyl morpholine oxide; the catalyst is compounded by a diluted hydrochloric acid solution with a mass concentration less than or equal to 20wt% and one or both of diethyl aluminum hypophosphite and inorganic aluminum hypophosphite; the defoaming agent is one or both of a polysiloxane defoaming agent and a polyether defoaming agent.
9. The method for preparing the fire-proof pre-reaction liquid according to claim 8, characterized in that: The steps include: Step S21), a carbonizing agent, a rheological additive, and deionized water are mixed in a weight ratio of 1-5:0.1-1:10-25, stirred at a stirring speed of less than 100 r / min for 40 minutes to form a uniform suspension, and allowed to stand for 12 hours to obtain a transparent and dynamically reversible gel material; Step S22) The first polyacrylamide-based organic / inorganic hybrid nanoparticles, the second polyacrylamide-based organic / inorganic hybrid nanoparticles, the cellulose solvent, the catalyst and the deionized water are mixed in a weight ratio of 58-353:61-352:0.5-4:0.5-2.5:10-30 to obtain a first fireproof mixed solution, Stir at room temperature at a stirring speed of less than 80r / min for 40 minutes to form a uniform suspension; then add 11 to 30 parts by weight of gelling material to the first fire-proof mixed liquid, and stir at room temperature at a stirring speed of less than 80r / min for 80 minutes to obtain a clear or slightly turbid second fire-proof mixed liquid; then add 0.5 to 2.5 parts by weight of catalyst and 0.001 to 0.05 parts by weight of defoaming agent to the second fire-proof mixed liquid in sequence, and stir at room temperature at a stirring speed of less than 80r / min for 40 minutes to obtain a fire-proof pre-reaction liquid, and let it stand for use.
10. The use of the fire-proof pre-reaction liquid according to claim 8, characterized in that: It is used for flame retardant treatment of transparent cellulose modified soda-lime glass products and forms a fireproof layer with a thickness of 0.02-0.3mm on the surface of the glass products. The specific operation is: spray the fireproof pre-reaction liquid onto the surface of the transparent cellulose modified soda-lime glass product, let it stand for 50 minutes, and after the surface of the glass product is dry, put it into a 50℃ oven for baking for 4 hours, and then heat it to 80℃ and bake for 3 hours, so that the cellulose on the glass surface and the fireproof pre-reaction liquid covering it form a multiple cross-linking system to form an interpenetrating network structure.
Citation Information
Patent Citations
Soap-free emulsion, fireproof liquid, preparation method and application of fireproof liquid
CN112708079A
Fireproof layer material, preparation method thereof, and fireproof glass
CN113929841A
Polylactic acid-based organic / inorganic hybrid nano-material, fireproof pre-reaction liquid, and preparation method and application of fireproof pre-reaction liquid
CN117264137A
Polylactic acid-based organic / inorganic hybrid material, fireproof pre-reaction liquid as well as preparation method and application of fireproof pre-reaction liquid
CN117264138A